An injectable silk sericin hydrogel promotes cardiac functional recovery after ischemic myocardial infarction. (1st September 2016) - Song, Yu; Zhang, Cheng; Zhang, Jinxiang; Sun, Ning; Huang, Kun; Li, Huili; Wang, Zheng; Huang, Kai; Wang, Lin
Graphical abstract: Abstract: Acute myocardial infarction (MI) leads to morbidity and mortality due to cardiac dysfunction. Here we identify sericin, a silk-derived protein, as an injectable therapeutic biomaterial for the minimally invasive MI repair. For the first time, sericin prepared in the form of an injectable hydrogel has been utilized for cardiac tissue engineering and its therapeutical outcomes evaluated in a mouse MI model. The injection of this sericin hydrogel into MI area reduces scar formation and infarct size, increases wall thickness and neovascularization, and inhibits the MI-induced inflammatory responses and apoptosis, thereby leading to a significant functional improvement. The potential therapeutical mechanisms have been further analyzed in vitro . Our results indicate that sericin downregulates pro-inflammatory cytokines (TNF-α and IL-18) and chemokine (CCL2) and reduces TNF-α expression by suppressing the TLR4-MAPK/NF-κB pathways. Moreover, sericin exhibits angiogenic activity by promoting migration and tubular formation of human umbilical vessel endothelial cells (HUVECs). Also, sericin stimulates VEGFa expression via activating ERK phosphorylation. Further, sericin protects endothelial cells and cardiomyocytes from apoptosis by inhibiting the activation of caspase 3. Together, these diverse biochemical activities of sericin protein lead to a significant recovery of cardiac function. This work represents the first study reporting sericin as an effective therapeutic biomaterial for ischemic myocardial repair in vivo . Statement of Significance: Intramyocardial biomaterial injection is thought to be a potential therapeutic approach to improve cardiac performance after ischemic myocardial infarction. In this study, we report the successful fabrication and in vivo application of an injectable sericin hydrogel for ischemic heart disease. We for the first time show that the injection of in situ forming crosslinked sericin hydrogel promotes heart functional recovery accompanied with reduced inflammatory responses, attenuated apoptosis and increased microvessel density in the infarcted hearts. Further, we reveal that the improvement in those aspects is ascribed to sericin protein's functional bioactivities that are comprehensively uncovered in this study. Thus, we identify sericin, a natural protein, as a biomaterial suitable for myocardial repair and demonstrate that the in vivo application of this injectable sericin hydrogel can be an effective strategy for treating MI.